PENGARUH PROGRAM TERINTEGRASI BKKBN TERHADAP PENINGKATAN KECERDASAN DAN KESEHATAN ANAK. - Madjid, T. Abdul (HEARTY, 2014)
The creation of a healthy child, a smart and cheerful one of which can be obtained through the education and construction done by cadres at BKKBN integrated programs . Based on the data analysis and discussion it can be concluded that :1. There is a direct positive BKKBN integrated program of child intelligence . That intelligence can be improved by implementing Son integrated program BKKBN well and true2. There is a direct positive influence on child health child intelligence. That intelligence can be enhanced by improving child health in opetimal child . Child's health is one factor that can be used to enhance alertness children, healthy children have the potential to be smart .3. There is a direct positive BKKBN integrated program of child health . This means that the child's health can be improved with the advent of integrated programs .